Plasticity : fundamentals and applications - Dixit, Prakash Mahadeo; Dixit, Uday S. (Boca Raton : Taylor & Francis, 2015)
'Preface Plastic deformation of metals is either desirable or undesirable depending on the situation. A structure or machine element should not undergo permanent deformation during the course of loading. Hence, the design is carried out so as to avoid plastic deformation. On the other hand, when the objective is to convert a raw material into a finished product, plastic deformation of the material is one option. Here, proper knowledge of plasticity is needed for process optimization. Sometimes, plastic deformation is desirable in situations where failure is inevitable. One example is the crash of an automobile, where a significant amount of plastic deformation of the vehicle body will protect the passengers from injury. In spite of the importance of plastic deformation, in most of engineering colleges, plasticity theory is not offered as a course in an undergraduate program. Many postgraduate programs in design and manufacturing also lack a course on plasticity. Lack of faculty and adequate textbooks contribute to this trend. A number of dissertations involving plasticity are carried out by students without a sound understanding of the basic concepts'--
Includes bibliographical references and index.
Keywords: Plasticity; Deformations (Mechanics); SCIENCE / Mechanics / General; TECHNOLOGY & ENGINEERING / Material Science; TECHNOLOGY & ENGINEERING / Metallurgy